Interpreting and linguistic inclusion – friends or foes? results from a field study. (3rd April 2018) - K. Pokorn, Nike; Čibej, Jaka
ABSTRACT: The article responds to the existing political claims that translation and interpreting reduce the incentive of recent immigrants to learn the language(s) of the host country and thereby impede their integration. To verify these claims, quantitative and qualitative research was conducted among asylum seekers in Slovenia, i.e. a group of recent immigrants who have access to free interpreting and translation services and free courses in the dominant language of the host country. A questionnaire was used to gather quantitative data on the language profiles of 127 current and former residents of the asylum seeker centres in Slovenia, while qualitative data were obtained through semi-structured interviews conducted with a representative group of 38 asylum seekers. The results show that all surveyed migrants had a positive attitude towards the host country language and that all of the interviewed migrants who had been in the host country for 7 months or more, regardless of their educational attainment, also took the state-funded course of the host country language. Additionally, although the provision of translation and interpreting is recognised as essential in high-risk situations, it is not the preferred communication strategy of the migrants, and therefore does not hinder their functional linguistic inclusion.